Tanggung Jawab Dokter/Rumah Sakit Akibat Malpraktik Medis Sebagai Upaya Perlindungan Hukum Bagi Pasien - Aris Priyadi (Faculty of Law, Universitas Wijayakusuma, 2024)
Abstract The relationship between a doctor and a patient is basically a civil law relationship, where the patient comes to the doctor to cure his illness and the doctor promises to try to treat or cure the illness. Civil relations are legal relations carried out by parties who are in equal positions. The relationship between the doctor and the patient gives rise to rights and obligations or in other words the agreement/agreement between the doctor and the patient gives rise to an obligation, in this case a business contract (inspanning verbintennis) because it is based on an obligation to do business. Doctors are obliged to provide care with care and attention in accordance with professional standards. So if the patient/family finds out that the doctor has not fulfilled his obligations as stated in the agreement, he can file a lawsuit for breach of contract before the court and ask for the agreement to be fulfilled and can demand compensation. Likewise, if a doctor in his service to a patient commits an act that violates the law, then in accordance with the provisions of Article 1365 of the Civil Code which regulates unlawful acts, the plaintiff (victim, patient) can demand compensation, both material and immaterial. The principle of the reverse burden of proof can be applied in medical cases, so the rights of the patient (plaintiff) will be protected, meaning that the plaintiff (patient), even though it is difficult or impossible to prove the fault of the defendant (doctor, hospital) and will still obtain his rights, namely in the form of compensation both material and immaterial. Keywords: Doctor's liability, malpractice, medical Abstrak Hubungan antara doker dengan pasien pada dasarnya merupakan hubungan hukum keperdataan, dimana pasien dating kepada dokter untuk disembuhkan penyakitnya dan dokter berjanji akan berusaha mengobati atau menyembuhkan penyakit tersebut. Hubungan keperdataan merupakan hubungan hukum yang dilakukan oleh pihak-pihak yang berada dalam kedudukan yang sederajat. Hubungan antara dokter dengan pasien tersebut menimbulkan hak dan kewajiban atau dengan kata lain perjanjian/persetujuan antara dokter dengan pasien menimbulkan perikatan, dalam hal ini perikatan usaha (inspanning verbintennis) karena didasarkan atas kewajiban berusaha. Dokter wajib memberikan perawatan dengan hati-hati dan penuh perhatian sesuai dengan standar profesi. Sehingga apabila pasien/keluarganya mengetahui bahwa dokter tidak memenuhi kewajibannya seperti yang tercantum dalam perjanjian, maka dapat menuntut gugatan wanprestasi ke muka sidang pengadilan dan meminta perjanjian tersebut dipenuhi serta dapat menuntut ganti rugi. Demikian pula apabila dokter dalam pelayanannya terhadap pasien melakukan perbuatan melanggar hokum, maka sesuai dengan ketentuan Pasal 1365 KUH Perdata yang mengatur perbuatan melanggar hukum, penggugat (korban,pasien) dapat menutut ganti rugi baik materiil maupun immateriil. Prinsip beban pembuktian terbalik dapat dterapkan dalam perkara medis, maka hak-hak pasien (penggugat) akan terlindungi artinya penggugat(pasien) walaupun sulit atau tidak bias membuktikan kesalahan tergugat (dokter,rumah sakit) dan tetap akan memperoleh hak-haknya yaitu berupa ganti rugi baik materiil maupun immateriil. Kata Kunci: Tanggung jawab dokter, malpraktik, medis